An Analysis of Current and Electric Field Pulses Associated With Upward Negative Lightning Flashes Initiated from the Säntis Tower. Issue 8 (26th April 2018) - He, Lixia; Azadifar, Mohammad; Rachidi, Farhad; Rubinstein, Marcos; Rakov, Vladimir A.; Cooray, Vernon; Pavanello, Davide; Xing, Hongyan
Abstract: We present a study on the characteristics of current and electric field pulses associated with upward lightning flashes initiated from the instrumented Säntis Tower in Switzerland. The electric field was measured 15 km from the tower. Upward flashes always begin with the initial stage composed of the upward‐leader phase and the initial‐continuous‐current (ICC) phase. Four types of current pulses are identified and analyzed in the paper: (1) return‐stroke pulses, which occur after the extinction of the ICC and are preceded by essentially no‐current time intervals; (2) mixed‐mode ICC pulses, defined as fast pulses superimposed on the ICC, which have characteristics very similar to those of return strokes and are believed to be associated with the reactivation of a decayed branch or the connection of a newly created channel to the ICC‐carrying channel at relatively small junction heights; (3) "classical" M‐component pulses superimposed on the continuing current following some return strokes; and (4) M‐component‐type ICC pulses, presumably associated with the reactivation of a decayed branch or the connection of a newly created channel to the ICC‐carrying channel at relatively large junction heights. We consider a data set consisting of 9 return‐stroke pulses, 70 mixed‐mode ICC pulses, 11 classical M‐component pulses, and 19 M‐component‐type ICC pulses (a total of 109 pulses). The salient characteristics of the current and field waveforms are analyzed. A new criterion is proposed to distinguish between mixed‐mode and M‐component‐type pulses, which is based on the current waveform features. The characteristics of M‐component‐type pulses during the initial stage are found to be similar to those of classical M‐component pulses occurring during the continuing current after some return strokes. It is also found that about 41% of mixed‐mode ICC pulses were preceded by microsecond‐scale pulses occurring in electric field records some hundreds of microseconds prior to the onset of the current, very similar to microsecond‐scale electric field pulses observed for M‐component‐type ICC pulses and which can be attributed to the junction of an in‐cloud leader channel to the current‐carrying channel to ground. Classical M‐component pulses and M‐component‐type ICC pulses tend to have larger risetimes ranging from 6.3 to 430 μs. On the other hand, return‐stroke pulses and mixed‐mode ICC pulses have current risetimes ranging from 0.5 to 28 μs. Finally, our data suggest that the 8‐μs criterion for the current risetime proposed by Flache et al. is a reasonable tool to distinguish between return strokes and classical M‐components. However, mixed‐mode ICC pulses superimposed on the ICC can sometimes have considerably longer risetimes, up to about 28 μs, as observed in this study. Key Points: Four types of pulses are identified in current and associated 15‐km electric field records of upward negative lightning flashes initiated from the Säntis Tower in Switzerland About 41% of mixed‐mode ICC pulses were associated with microsecond‐scale electric field pulses occurring some hundreds of microseconds prior to the onset of the current The characteristics of M‐component‐type pulses occurring during the initial stage (ICC pulses) are found to be similar to those of classical M components occurring during the continuing current after return strokes